Escola Família Agrícola Jaguaribana Zé Maria do Tomé : educação do campo e territorialização da agroecologia - Almeida, João Paulo Guerreiro de (2024)
The Agricultural Family School Jaguaribana Zé Maria do Tomé, located in the Olho D'água dos Currais community, municipality of Tabuleiro do Norte-Ceará, is one of the eight EFAs in that state, whose operations are broad and expand beyond municipal dynamics, by It is a school engaged and articulated with institutions, collectives and social movements linked to resistance in defense of Agroecology. In addition to offering an Agricultural Technical Course, EFA Jaguaribana, through its Association, develops agroecological projects with peasants in the Jaguaribana region. In this research, linked to the Popular Education line of the Postgraduate Program in Education at the Federal University of Paraíba, we pursue the following question: How does EFA Jaguaribana Zé Maria do Tomé, through the various fronts of action, build community strategies of resistance to Agribusiness, from the perspective of Rural Education and Popular Education, with a view to the territorialization of Agroecology in Vale do Jaguaribe? In this sense, the objective of this work was to analyze the educational and community activities of the Agricultural Family School Jaguaribana Zé Maria do Tomé, with regard to strategies for training the rural population to live in the semi-arid region of Ceará, while interrogates its possible contributions to the organization and sociopolitical participation of peasants, built through the territorialization of Agroecology in Vale do Jaguaribe. To develop the research, we analyzed references relevant to Rural Education (Silva, 2020; Molina, 2010; Caldart, 2008; Carvalho, 2006), Alternation Pedagogy (Gimonet, 2007; Begnami, 2003 and 2019) and Agroecology (Caporal, 2011; Caporal and Costabeber, 2004; Machado and Machado Filho, 2017; Guhur and Silva, 2022), followed by its interfaces with Popular Education. The institutional documents of the School and the Association, such as the Pedagogical Political Project and Institutional and non-institutional Memoirs (photographs, bulletins, cards and others) were also consulted, in order to understand their identity and systematize the main activities carried out. In field research, we carried out on-site observations, at EFA Jaguaribana itself and in peasant communities where agroecological projects are developed, aiming to understand the strategies and contributions of this educational institution to the organization and socio-political participation of peasants. At these moments, the various subjects who make up EFA Jaguaribana were also interviewed, as a way of understanding their operating dynamics and the process of territorialization of Agroecology in Vale do Jaguaribe. From this research, we identified that such action aimed at the development of peasant territories and the agroecological transition promotes the territorialization of Agroecology, which is preceded by community insertion and educational-political processes, crossed by Popular Education and Rural Education, consequently, forms of liberating education that encourage organization and popular participation. We conclude that EFA Jaguaribana, through its actions, ratifies the social function of a rural school, reducing the school-community distance, through its expansion to peasant communities with the Technical Course and the Projects developed, from an agroecological perspective. Nevertheless, this dynamic of insertion in peasant territories implies a way of expanding the possibilities of action/training in the Pedagogy of Alternation, conferring particular characteristics and demands of the semi-arid region and the Vale do Jaguaribe.